2021
DOI: 10.3892/etm.2021.11093
|View full text |Cite
|
Sign up to set email alerts
|

Fate of hematopoietic stem cells determined by Notch1 signaling (Review)

Abstract: Regulation of the fate of hematopoietic stem cells (HSCs), including silencing, self-renewal or differentiation into blood line cells, is crucial to maintain the homeostasis of the human blood system and prevent leukemia. Notch1, a key receptor in the Notch signaling pathway, plays an important regulatory role in these properties of HSCs, particularly in the maintenance of the stemness of HSCs. In recent decades, the ubiquitination modification of Notch1 has been gradually revealed, and also demonstrated to af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 137 publications
0
2
0
Order By: Relevance
“…We also found that senescence 𝛽-Gal staining in testes was mainly concentrated in LCs and not spermatogenic tissue. Considering that LCs play a core role in maintaining reproductive and endocrine functions, [36,37] we concluded that prenatal DEHP exposure induced testicular aging by promoting LC senescence.…”
Section: Discussionmentioning
confidence: 89%
“…We also found that senescence 𝛽-Gal staining in testes was mainly concentrated in LCs and not spermatogenic tissue. Considering that LCs play a core role in maintaining reproductive and endocrine functions, [36,37] we concluded that prenatal DEHP exposure induced testicular aging by promoting LC senescence.…”
Section: Discussionmentioning
confidence: 89%
“…Notch1 and its ligands are part of an evolutionarily conserved signalling pathway that is essential for endothelial cell-fate determination (Artavanis-Tsakonas et al, 1999). The Notch signalling pathway has been implicated in a variety of roles including angiogenesis (Hyun et al, 2022), neurogenesis (Wang et al, 2009), limb development (Francis et al, 2005) and haematopoiesis (Ge et al, 2021), but its role as a mechanosensor has only recently been defined (Mack et al, 2017). Through a series of in vitro and in vivo murine knockdown models, Mack et al (2017) demonstrated that Notch1 was responsible for cell elongation, alignment, junctional integrity and endothelial quiescence in response to laminar flow (Mack et al, 2017).…”
mentioning
confidence: 99%